Monospecific Diatom Cultures Suggest Potential Interspecies Variation of Diatom‐Bound Nitrogen Isotope Signatures Associated With Silica Acquisition - R. S. Robinson; C. A. Jones; I. A. Dove; R. P. Kelly; M. A. Brzezinski (Geochemistry, Geophysics, Geosystems)
Abstract Tracking the supply and demand of nitrate in the past ocean can help to constrain the role of biology and circulation in regulating climate. The nitrogen isotopic composition of marine phytoplankton (δ15Nbiomass) tracks nitrate supply and demand but may not be well preserved in the sediments, while the isotopic composition of nitrogen contained within the frustules of diatoms (δ15NDB) is thought to be protected from alteration. Here we document the relationship between δ15Nbiomass and δ15NDB in cultures of seven Southern Ocean diatom species. Average δ15Nbiomass values are 1.8 ± 0.8‰ lower than δ15NDB values for 6 of the 7 species grown. The exception, Fragilariopsis rhombica, records δ15Nbiomass that are greater than δ15NDB values, opposite in sign from the other studied species and statistically significantly different from each other. Because most of the diatom species measured indistinguishable isotopic offsets between biomass and diatom‐bound N, we assert that sedimentary δ15NDB values largely reflect surface ocean nitrate δ15N and therefore nitrate supply and demand. F. rhombica was not only different in terms of its relationship between δ15Nbiomass and δ15NDB but also in mean N:Si uptake and nitrogen content of cleaned frustules, suggesting a role for N allocation relative to Si in setting δ15NDB. While this result is largely based on only one species of diatom in culture, it is possible that significant contribution of groups with a similarly elevated εDB could decrease the overall value of the sedimentary δ15NDB signal.